PERSEPSI TERHADAP KONSUMSI KOPI DAN TEH MAHASISWA TPB-IPB TAHUN AJARAN 2007-2008 - Febriana Ira Dewi; Faisal Anwar; Leily Amalia (Jurnal Gizi dan Pangan, 2009)
Design of this research is a cross sectional study and study site in Bogor Agricultural Institute, Bogor. A total of 354 samples was drawn randomly. Average daily coffee and tea consumption were about 20.4 g and 1.93 g. Coffee is usually consumed at night. Whereas, tea is consumed in the morning. Samples feel positive and negative effects after consumption of coffee and tea such us sleepless, fatigue, fresh, easy to concentrate, addiction, diuresis, and cardiac arrhythmias.